2019
DOI: 10.3390/su11030884
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of Secondary Deformations Captured by Satellite Radar Interferometry: Case Study of an Abandoned Coal Basin in SW Poland

Abstract: The issue of monitoring surface motions in post-mining areas in Europe is important due to the fact that a significant number of post-mining areas lie in highly-urbanized and densely-populated regions. Examples can be found in: Belgium, the Czech Republic, France, Germany, the Netherlands, Spain, the United Kingdom, as well as the subject of this study, the Polish Walbrzych Hard Coal Basin. Studies of abandoned coal fields show that surface deformations in post-mining areas occur even several dozen years after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Land subsidence due to mining is mainly caused by removing a deposit from a rock mass and forming a post-mining void [46]. This type of land subsidence can damage the surface and underground infrastructure and endanger surface users' safety [8,[47][48][49][50][51]. Land subsidence's spatial extent and value are primarily determined by the depth of exploitation, seam thickness, panel dimensions, overlying rock mass geomechanical conditions, geological defects, surface topography, production methods and post-mining void reclamation method [30,52,53].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Land subsidence due to mining is mainly caused by removing a deposit from a rock mass and forming a post-mining void [46]. This type of land subsidence can damage the surface and underground infrastructure and endanger surface users' safety [8,[47][48][49][50][51]. Land subsidence's spatial extent and value are primarily determined by the depth of exploitation, seam thickness, panel dimensions, overlying rock mass geomechanical conditions, geological defects, surface topography, production methods and post-mining void reclamation method [30,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Land subsidence's spatial extent and value are primarily determined by the depth of exploitation, seam thickness, panel dimensions, overlying rock mass geomechanical conditions, geological defects, surface topography, production methods and post-mining void reclamation method [30,52,53]. Many research papers have been presented in recent years documenting the land subsidence phenomenon caused by mining [47,49,[54][55][56][57][58][59][60][61][62][63]. As a result, one can be stated that the spatial extent of the phenomenon can range from several km 2 [49] to tens of km 2 [15], while its values can range from a few mm/year [64] to several cm/day [65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring and controlling the subsidence of runways are of great significant to ensure the safe operation of the whole airport and avoid the potential extensive loss of life and property.During the last three decades, interferometric synthetic aperture radar (InSAR) technology has developed into a powerful tool, providing high-resolution, day-and-night, weather-independent wide-coverage and high-accuracy measurements of the earth surface [6]. It has been widely used in various applications, such as the displacements monitoring of city subsidence [7][8][9][10][11][12], important infrastructures [13][14][15][16] and landslides geohazards [17][18][19][20][21]. Compared to traditional geodetic measuring methods-e.g., leveling and global positioning system (GPS)-InSAR measurements do not need any on-site installation and power supply, thus they will not have any impact on the regular operation of the airport.…”
mentioning
confidence: 99%
“…Blachowski et al [12], in their paper entitled "Evolution of Secondary Deformations Captured by Satellite Radar Interferometry: Case Study of an Abandoned Coal Basin in SW Poland", used multi-temporal ERS-1, ERS-2, and Envisat C-band synthetic aperture radar (SAR) images to analyze ground movements of an enclosed coal mining basin known as Walbrzych Coal Basin in the southwestern part of Poland from 1995 to 2010. The results showed that (1) the post-mining ground motion process is very complex, and (2) the SAR interferometric (InSAR) technique has a distinct advantage that it can be used for historical studies.…”
Section: Sustainable Applications Of Rs and Gis Technologiesmentioning
confidence: 99%